The Structure of Social Disparities in Education : Gender and Wealth - Filmer, Deon (The World Bank, 2000)
January 2000 - Wealth gaps in educational outcomes are large in many developing countries. And gender gaps, though absent in many societies, are large in some, particularly in South Asia and North, Western, and Central Africa. In some countries with a female disadvantage, household wealth interacts with gender to create an especially large gender gap among the poor. Using internationally comparable household data sets (Demographic and Health Surveys), Filmer investigates how gender and wealth interact to generate within-country inequalities in educational enrollment and attainment. He carries out multivariate analysis to assess the partial relationship between educational outcomes and gender, wealth, household characteristics (including level of education of adults in the household), and community characteristics (including the presence of schools in the community). He finds that: · Women are at a great educational disadvantage in countries in South Asia and North, Western, and Central Africa. · Gender gaps are large in a subset of countries, but wealth gaps are large in almost all of the countries studied. Moreover, in some countries where there is a heavy female disadvantage in enrollment (Egypt, India, Morocco, Niger, and Pakistan), wealth interacts with gender to exacerbate the gap in educational outcomes. In India, for example, where there is a 2.5 percentage point difference between male and female enrollment for children from the richest households, the difference is 34 percentage points for children from the poorest households. · The education level of adults in the household has a significant impact on the enrollment of children in all the countries studied, even after controlling for wealth.